Proceso de Ejecución de pago de Sueldos al personal IESS Milagro - Velásquez Vargas, Yessenia Dayanara (2017)
The present project was carried out at the Hospital General Milagro of the IESS, currently this hospital unit has 637 employees, including contracted personnel and plant, the purpose of this project is to know the process of payroll from where it is born until the end of the systems immersed in the course of payment of salaries to the personnel who work, times, problems, benefits and risks, for that reason the subject is the Process of Execution of Payment of Salaries to the staff of the IESS Milagro. For the development of the same will be conducted interviews with the current Responsible Human Talent Area, in order to know the topic and clear doubts as to the drafting of the project, The line of research to be applied will be financial management and social commitment , because the results are either positive or negative the result is directed to the servers, the consequences of the risks and problems.